2003
DOI: 10.1088/0964-1726/13/1/003
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative health monitoring of bolted joints using a piezoceramic actuator–sensor

Abstract: The non-destructive evaluation technique using a piezoceramic (PZT) as an actuator-sensor has a potential to efficiently detect structural damage. In this technique, a PZT actuator-sensor patch is bonded on a structure. Through the measurement of its electrical impedance, which is related to the mechanical impedance of the structure being bonded, the change in structural properties due to damage can be detected. This paper presents the use of a PZT actuator-sensor in conjunction with numerical model-based meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
102
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(102 citation statements)
references
References 25 publications
0
102
0
Order By: Relevance
“…In addition to the studies on modeling of this method, there have been other researchers who conducted studies on adequacy of this method in detection and evaluation of looseness of bolted structures. Ritdumrongkul et al, besides modeling the electrical impedance of a structure, studied the efficiency of the method empir- ically, having a wave dispersal approach; while they provided indices to quantify the amount of looseness, they examined the sensitivity of indices to firmness and attenuation of joints (Ritdumrongkul, et al, 2004). Providing an index for evaluation of the looseness of bolts, Park et al surveyed the efficiency of the method in detecting looseness in bolted joints of pipelines (Overly, et al, 2007;Park, et al, 2001).…”
Section: Impedance Based Methodsmentioning
confidence: 99%
“…In addition to the studies on modeling of this method, there have been other researchers who conducted studies on adequacy of this method in detection and evaluation of looseness of bolted structures. Ritdumrongkul et al, besides modeling the electrical impedance of a structure, studied the efficiency of the method empir- ically, having a wave dispersal approach; while they provided indices to quantify the amount of looseness, they examined the sensitivity of indices to firmness and attenuation of joints (Ritdumrongkul, et al, 2004). Providing an index for evaluation of the looseness of bolts, Park et al surveyed the efficiency of the method in detecting looseness in bolted joints of pipelines (Overly, et al, 2007;Park, et al, 2001).…”
Section: Impedance Based Methodsmentioning
confidence: 99%
“…Structural health monitoring (SHM) has made significant advances in the past decades [1][2][3][4][5][6][7][8]. Monitoring of refractories, which are widely used in furnace, iron, and steel industries due to their ability to gain strength rapidly and to withstand aggressive environments and high temperature [9], receives increasing attention [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The analytical relationship between the piezoelectric impedance and the mechanical impedance of the host structure was established for the first time. Sopon et al [18] used a piezoelectric transducer (PZT) as an actuator-sensor collectively in conjunction with the numerical model-based spectral element method (SEM) in structural health monitoring to quantitatively detect damage of bolted joints. By analyzing the characteristics of the piezoelectric element under the bolt looseness condition, Gao et al [19] concluded that the conductance of the piezoelectric patches changes significantly under the high-frequency (more than 50 kHz) voltage excitation.…”
Section: Introductionmentioning
confidence: 99%